Transcriptional Profiling of Dendritic Cells in a Mouse Model of Food‐Antigen‐Induced Anaphylaxis Reveals the Upregulation of Multiple Immune‐Related Pathways. Issue 3 (17th December 2018) - Rodriguez, Maria Jose; Palomares, Francisca; Bogas, Gador; Torres, Maria Jose; Diaz‐Perales, Araceli; Rojo, Javier; Plaza‐Seron, Maria del Carmen; Rodriguez‐Nogales, Alba; Orengo, Christine; Mayorga, Cristobalina; Perkins, James Richard
Abstract : Scope: Much of the knowledge about gene expression during anaphylaxis comes from candidate gene studies. Despite their potential role, expression changes in dendritic cells (DCs) have not been studied in this context using high throughput methods. The molecular mechanisms underlying food‐antigen‐induced anaphylaxis are investigated using DCs from an animal model. Methods and results: RNA sequencing is used to study gene expression in lymph‐node‐derived DCs from anaphylactic mice sensitized intranasally with the major peach allergen Pru p 3 during the acute reaction phase, induced intraperitoneally. In total, 237 genes changed significantly, 181 showing at least twofold changes. Almost three‐quarters of these increase during anaphylaxis. A subset is confirmed using RT‐PCR in a second set of samples obtained from a new batch of mice. Enrichment analysis shows an overrepresentation of genes involved in key immune system and inflammatory processes, including TGF‐β signaling. Comparison with a study using anaphylactic human subjects show significant overlap. Conclusions: The findings provide a comprehensive overview of the transcriptional changes occurring in DCs during anaphylaxis and help elucidate the mechanisms involved. They add further weight to the putative role of these cells in anaphylaxis and highlight genes that may represent potential therapeutic targets. Abstract : Mice are sensitized to the major peach allergen Pru p 3 using a previously published protocol. Upon challenge with the specific allergen, they underwent an anaphylactic reaction. Dendritic cells are isolated from their lymph nodes, from which RNA is extracted and sequenced, comparing the results to non‐anaphylactic, non‐sensitized mice to look for differences in gene expression in a high‐throughput manner. Differential expression is found for over 200 genes and multiple immune pathways, including complement activation, LPS signaling, and TGF‐β pathways.